Male reproductive system inflammation after healing from coronavirus disease 2019. (14th December 2021) - Morselli, Simone; Sebastianelli, Arcangelo; Liaci, Andrea; Zaccaro, Claudia; Pecoraro, Alessio; Nicoletti, Rossella; Manera, Alekseja; Bisegna, Claudio; Campi, Riccardo; Pollini, Simona; Antonelli, Alberto; Lagi, Filippo; et al.
Abstract: Background: There is evidence that, after severe acute respiratory syndrome coronavirus 2 infection, male reproductive function and semen quality may be damaged Objectives: To evaluate a panel of inflammatory mediators in semen in patients recovered from coronavirus disease 2019. Material and methods: Sexually active men with previous severe acute respiratory syndrome coronavirus 2 infection and proven recovery from coronavirus disease 2019 were enrolled in a prospective cohort study. Clinical, uro‐andrological data and semen specimens were prospectively collected. For previously hospitalized coronavirus disease 2019 patients, data on serum inflammatory markers were retrospectively collected. Results: A total of 43 men were enrolled in the study. Of these, 32 men were normozoospermic, three were oligozoospermic, and eight were crypto‐azoospermic. Serum inflammatory markers (procalcitonin and C‐reactive protein) were analyzed in previously hospitalized patients both at admission and at peak of infection. Levels at admission were statistically significantly higher in patients resulting in crypto‐azoospermic with respect to those resulting in normozoospermic ( p = 0.05; p = 0.03 and p = 0.02, respectively) after healing. Seminal cytokine levels were similar among all groups. Interleukin‐1β and tumor necrosis factor‐α levels were significantly negatively related to sperm total number and concentration, whereas interleukin‐4 was correlated with sperm motility. Discussion and conclusion: Negative correlations between interleukin‐1β and tumor necrosis factor‐α and sperm number and the overall high levels of semen cytokines indicate a potential detrimental role of severe acute respiratory syndrome coronavirus 2 driven inflammation on spermatogenesis. Overall, our results indicate that male patients recovering from coronavirus disease 2019 deserve accurate follow‐up for their fertility status.